Exposure to carcinogenic primary aromatic amines and associated health risks among the Chinese general population: A nationwide biomonitoring study - Yanan Yao; Jingchuan Xue; You Wang; Kurunthachalam Kannan; Tao Zhang (Environmental Chemistry and Ecotoxicology, 2025)
Primary aromatic amines (PAAs) are a class of chemicals that are produced in large quantities and used widely. However, studies on internal exposure levels of these chemicals in the general population in China are limited. This study presents a nationwide survey of 25 PAAs by analyzing 457 urine samples collected from 16 cities across China during 2022, using ultra-performance liquid chromatography–tandem mass spectrometry (UPLC-MS/MS). All 25 target PAAs were detected, with aniline, meta-toluidine, ortho-toluidine (o-TD), para-toluidine (p-TD), 4-ethoxyaniline (4-EA), and 3,4-diaminoanisole as major compounds. The sum median concentrations of all PAAs (ΣPAAs) ranged from 0.93 to 3.8 ng/mL across the cities. Urinary PAA levels significantly varied depending on demographic, geographic, and socioeconomic factors, with higher concentrations observed among smokers, non-adults, and residents from industrialized or ethnically distinct cities. The urinary concentrations of ΣPAAs were also significantly correlated with gross domestic product (GDP) and GDP per capita of select Chinese cities. Hazard quotient was calculated from exposure to PAAs and values were < 1, indicating minimal risks to the Chinese population. However, multiple linear regression revealed significant positive correlations (p < 0.05) between PAAs and an oxidative stress biomarker (8-hydroxy-2′-deoxyguanosine). Multi-contaminant models identified 4-EA, o-TD, and p-TD as major contributors to oxidative DNA damage. This study provides baseline data on human internal exposure to PAAs, highlights factors influencing exposure and potential health risks, and offers evidence to support future public health policies aimed at reducing exposure in high-risk populations.